Robust Model-Free Fault-Tolerant Predictive Control for PMSM Drive System - Shu Cheng; Ruirui Zhou; Zhuoxin Li; Zhen Xi; Jundong Zhao; Kaihui Zhao; Chaoqun Xiang (IEEE Access, 2024)
The parameter mismatch caused by the parameter uncertainties and unknown disturbances degrades the performance of finite-control-set model predictive control (FCS-MPC). This paper presents a model-free fault-tolerant predictive control (MFFTPC) method based on an extended sliding mode observer (ESMO) for the surface-mounted permanent magnet synchronous motor (SPMSM) drive system. First, considering parameter uncertainties and unknown disturbances, a novel ultra-local model (ULM) is established for the PMSM drive system. Next, a finite-control-set model-free fault-tolerant predictive current controller (FCS-MFFTPCC) is designed in the current loop, and the model-free deadbeat fault-tolerant predictive speed controller (MFDFTPSC) is designed in the speed loop. Then, unknown parts of the novel ULM are estimated by the designed ESMO and compensated for the errors caused by the parameter mismatches. Thus, the presented method reduces the dependence on the precise model and eliminates the effect caused by parameter mismatches on the MPC control performance of the SPMSM drive system.